Characterization of a Novel Nuclear Specific Dicer-isoform in Human Cells - Alquraish, Fatema H. (KAUST Research Repository, 2019)
For more than a decade, studies focused on RNA interference (RNAi) pathway as a pivotal gene regulatory mechanism. RNAi components are attracting considerable interest due to the recent evidence demonstrating that they play a role not only in post-transcriptional regulation but also in transcriptional level. The involvement of RNAi components in heterochromatin formation and RNA Pol II processivity and alternative splicing in different organisms has been shown. Dicer protein, a highly conserved protein among kingdoms, is one of the main effectors in this pathway. There is a considerable amount of literature on Dicer’s role in the cytoplasm; however, there is still vast ambiguity concerning nuclear Dicer. More recent evidence reveals the existence of Dicer1 variants that are differentially expressed in some cancer cells. Our experiments set out to investigate one of these variants that we hypothesise is responsible for the nuclear function. We undertook genomic and biochemical approaches applied to HAP 1 cells as a model system to characterise Dicer1-s, taking advantage of a custom-made antibody in our research group. Here, as anticipated, our experiments proved that Dicer1-s is enriched in the nuclear compartment compared to full-length Dicer1, indicating that it might be a putative contributor to nuclear gene regulation activity. Unfortunately, it was not possible to establish a mutant cell line to investigate the significant nuclear function of Dicer1-s, due to the need for further optimisation of the methods used. Exploitation of previously optimised gene knock-out tools might accelerate shedding light on protein, DNA, and RNA partners, disclosing the exact nuclear mechanisms that might exhibit similar activity.